Electronics, automation and engineering of power systems : selected, peer reviewed papers from the International Forum on Electrical Engineering and Automation & the 2014 International Conference on Lighting Technology and Electronic Engineering (ICLTEE 2014), November 29-30, 2014, Guangzhou, China - Liang, Rongqing (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the International Forum on Electrical Engineering and Automation & the 2014 International Conference on Lighting Technology and Electronic Engineering (ICLTEE 2014), November 29-30, 2014, Guangzhou, China. The 191 papers are grouped as follows: Chapter 1: Sensors, Measurements, Systems of Monitoring, Detection and Diagnostics; Chapter 2: Mechatronics, Robotics, Control and Automation; Chapter 3: Technologies of Intelligent Systems; Chapter 4: Practice of Data Processing for Intelligent Systems; Chapter 5: Power Systems Engineering; Chapter 6: P.